Aircraft’s U-turn Maneuvers applied in 3-Dimensional scene driven - Jiening Wang; Jiang Qu; Mei Dong (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
U-turn maneuver is a special taxiing behavior on the ground. This paper studied the behavior and aimed to research the problem of position and attitude during the movement. From the perspective of airport tower control simulation, the calculation methods that the aircraft did U-turn maneuver under the nonholonomic constraints were proposed. According to the real geometrical constraints and kinematic equations, a method, suitable for simulation, deduction and calculation, was designed. At last, with the help of MATLAB, the validity of this method was confirmed. Compared with dynamics model, this method was easy to be computed and more suitable for the application to scene driven. This paper, moreover, designed the structural frame of 3D scene driven for the tower control simulation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4495